Effects Of Technology On Foreign Language Learning And Its Negative Impacts: An Overview - ZANYAR GHAFAR; Ayu; Melani Nur Cahya (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
Background: Because of the tremendous progress that has taken place throughout the globe in a number of categories, including as the social, the economic, the educational, and so on, the ties that exist between countries are today usually considered to be in a very favorable state. As a result of these kinds of encounters, there is now a higher requirement for persons to be able to communicate successfully in a minimum of two languages. Aim: The study’s goal is to find out the significance that is placed on being able to successfully communicate in a foreign language, there has been a rise in the use of both classic and modern methods for the teaching of language rely on Technological devices. At this point in time, there is no other degree of technical innovation that can compete with it. Method: Technology's effects on foreign language education were examined through studying technology's damages. Technology in foreign language instruction and its negative impacts were examined. This research was conducted with the intention of bringing to light the possibly negative effects that students who are making an effort to learn a foreign language as a result of utilizing technology may go on to suffer. Findings: The purpose of this article is to reveal how the speed and ease of technology, when used incorrectly, can cost students more time than they intend to spend learning a language. This article's specific goal is to show how something similar may ultimately occur in the actual world.